Potential role of long non-coding RNA (nuclear paraspeckle assembly transcript 1 and metastasis associated lung adenocarcinoma transcript 1) in periodontitis pathogenesis: A systematic review - Al-Mufti , Saif M; Abdulkareem , Ali A; Milward , Mike; Cooper , Paul R (Journal of Baghdad College of Dentistry, 2024)
Background: Dysregulation of Long non-coding (lnc)RNAs has been linked to periodontitis, with potential importance in disease onset and progression. These lncRNAs potentially modulate inflammatory/immune responses during periodontitis. This review aimed to highlight the potential role of Nuclear Paraspeckle Assembly Transcript (NEAT)1 and Metastasis Associated Lung Adenocarcinoma Transcript (MALAT)1 lncRNAs in periodontitis pathogenesis. Methods: A literature search of three electronic databases was performed in SCOPUS, MEDLINE (PubMed) and EMBASE using search terms linking periodontitis/periodontal disease with NEAT1 and MALAT1 lncRNAs. Duplicate publications were removed from the retrieved articles which were then filtered to include the most relevant papers for evidence synthesis. Results: Nine studies (in vitro and in vivo) were included in the final analysis. The total number of studies investigating the role of NEAT1 and MALAT1 in pathogenesis of periodontitis was 4 and 5, respectively. The findings indicated gene expression changes of NEAT1 and MALAT1 in periodontitis compared with periodontal health. Conclusion: No concrete evidence could be withdrawn from this review; however, results suggested that lncRNAs, NEAT1 and MALAT1 could be involved in periodontitis pathogenesis. However, further in vivo studies are required to confirm these findings.